A vacancy composite diaphragm and its preparation method, application and lithium-based liquid battery based on the vacancy composite diaphragm, and a solid-state battery

By using vacancy composite separators, using Te-rich vacancy particles to capture anions and promote lithium ion migration, the problem of synchronous improvement of existing lithium-based battery separators in improving lithium ion conductivity and migration number is solved, and the high magnification of lithium ion batteries is achieved Performance and long cycle stability.

CN116345065BActive Publication Date: 2025-02-07HARBIN INST OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310136500.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-02-07
Estimated Expiration
2043-02-20

AI Technical Summary

Technical Problem

The existing lithium-based battery separators have difficulties in synchronously improving the conductivity and migration number of lithium-ion. At the same time, the use of ceramic particles leads to blockage of the membrane pores, affecting high-rate performance and long-cycle stability.

Method used

Using a vacant composite separator, the gelatinous separator dispersion prepared from the separator base polymer powder, Te-rich vacant particles, organic solvents and deionized water is prepared by scraping. The Te-rich vacant particles effectively capture the anions in the electrolyte and promote lithium. Rapid migration of ions.

Benefits of technology

It significantly improves the high-rate performance and long-cycle stability of lithium-ion batteries, and at the same time improves the wetting and storage capacity of the diaphragm to the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116345065B_ABST
    Figure CN116345065B_ABST
Patent Text Reader

Abstract

A vacancy composite diaphragm and its preparation method, application and lithium-based liquid battery based thereon, as well as a solid-state battery. The present invention belongs to the field of lithium battery diaphragms. The present invention is to solve the technical problems that the existing lithium-based batteries cannot achieve the simultaneous improvement of lithium ion conductivity and lithium ion migration number, and the existing modification method using ceramic particles directly coated or as fillers leads to diaphragm pore blockage, which is not conducive to the high rate performance and long cycle stability of lithium ion batteries. The present invention adds Te-rich vacancy particles to the diaphragm substrate to obtain a vacancy composite diaphragm with uniform pore size, precisely controllable thickness, high lithium ion conductivity, high lithium ion migration number, good electrolyte absorption rate and good wettability. The introduction of Te-rich vacancy particles effectively limits the migration of anions in the electrolyte, greatly improves the migration ability of lithium ions, and can also homogenize lithium ion deposition, inhibit the growth of lithium dendrites, and improve the rate performance and cycle stability of lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium battery diaphragms, and specifically relates to a vacancy composite diaphragm and a preparation method and application thereof, a lithium-based liquid battery based thereon, and a solid-state battery. Background Art

[0002] As an important part of energy conversion, the application of chemical power sources has become more and more widespread. Among them, lithium-based batteries have rapidly replaced other secondary batteries in the field of consumer electronics due to their advantages such as high operating voltage, high energy density, long cycle life, and no memory effect. They have also begun to be commercially applied in electric vehicles, hybrid vehicles, large-scale energy storage, etc. In the context of many countries announcing that they will eliminate vehicles fueled by gasoline or diesel by 2040, people have put forward higher requirements for the energy density, endurance, fast charging performance and safety of lithium-based batteries.

[0003] However, the existing commercial lithium-based battery separators are limited by the migration of anions in the electrolyte in the separator, and the lithium ion conductivity and lithium ion migration number are both low. Therefore, the contribution rate of commercial separators to the high-rate performance of batteries is very low. At present, the mainstream strategies for regulating the ion transport behavior in the separator mainly include constructing an ordered pore structure on the separator, coating lithium-philic materials on the surface of the separator, and introducing anion adsorbents. These strategies have achieved some results, but it is difficult to achieve the improvement of lithium ion conductivity and lithium ion migration number at the same time, and it is difficult to achieve large-scale preparation and commercial application. Therefore, it is of great practical application significance to develop new lithium-ion battery composite separators and simultaneously achieve high rate, high energy density and long cycle stability of lithium-ion batteries. Summary of the invention

[0004] The present invention aims to solve the technical problems that the existing lithium-based batteries cannot achieve the simultaneous improvement of lithium ion conductivity and lithium ion migration number, and the existing modification method using ceramic particles directly coated or used as fillers leads to clogging of diaphragm pores, which is not conducive to the high rate performance and long cycle stability of lithium-ion batteries. The present invention provides a vacancy composite diaphragm and its preparation method, application and lithium-based liquid battery based on the diaphragm, as well as a solid-state battery.

[0005] One of the purposes of the present invention is to provide a vacancy composite diaphragm, which is prepared by knife coating a colloidal diaphragm dispersion prepared from diaphragm base polymer powder, Te-rich vacancy particles, an organic solvent and deionized water.

[0006] It is further defined that the membrane substrate polymer powder is one or a mixture of any proportion of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polyacrylic acid and polyacrylonitrile.

[0007] It is further defined that the Te vacancy-rich particles are one or a mixture of any ratio of bismuth telluride, N-type bismuth telluride, and P-type bismuth telluride.

[0008] It is further defined that the mass ratio of the Te vacancy-rich particles to the membrane substrate polymer powder is (5-50):100.

[0009] It is further defined that the particle size of the Te vacancy-rich particles is 400-2000 nm.

[0010] It is further defined that the molecular weight of the membrane base polymer powder is 500,000-1.5 million.

[0011] The second object of the present invention is to provide a method for preparing a vacancy composite diaphragm, wherein the method for preparing the vacancy composite diaphragm is carried out according to the following steps:

[0012] Step 1: Disperse the Te vacancy-rich particles in an organic solvent and perform ultrasonic treatment at room temperature for 1 h to 3 h to obtain a Te vacancy-rich particle dispersion;

[0013] Step 2: adding the membrane base polymer powder to the Te vacancy-rich particle dispersion obtained in step 1, and magnetically stirring at 50-70° C. for 0.5 h-1 h to obtain a colloidal dispersion;

[0014] Step 3: adding deionized water dropwise to the colloidal dispersion obtained in step 2, stirring magnetically at 50-70° C. for 0.5 h-1 h, and cooling to room temperature to obtain a colloidal diaphragm dispersion;

[0015] Step 4: Scrape the colloidal diaphragm dispersion obtained in step 3 onto the substrate and dry it at room temperature to obtain a vacancy composite diaphragm.

[0016] It is further defined that the organic solvent in step 1 is one or a mixture of any ratio of acetone, N-methylpyrrolidone, N-N-dimethylformamide, and N-N-dimethylacetamide.

[0017] It is further defined that the mass ratio of the membrane substrate polymer powder in step 2 to the Te vacancy-rich particles in step 1 is 100:(5-50).

[0018] It is further defined that the mass ratio of the membrane substrate polymer powder in step 2 to the organic solvent in step 1 is 1:(6-10).

[0019] It is further defined that the rotation speed of the magnetic stirring in step 2 is 500 r / min to 2500 r / min.

[0020] It is further defined that the mass ratio of the deionized water in step 3 to the organic solvent in step 1 is (3-5):100.

[0021] It is further defined that the rotation speed of the magnetic stirring in step 3 is 500 r / min to 2500 r / min.

[0022] It is further defined that the thickness of the vacancy composite membrane in step 4 is 8 μm to 50 μm.

[0023] The third object of the present invention is to provide an application of the above-mentioned vacancy composite diaphragm in a lithium-based liquid battery.

[0024] It is further defined that lithium-based liquid batteries include lithium metal batteries, lithium-ion batteries, lithium-sulfur batteries, lithium-based dual-ion batteries and lithium-CO2 batteries.

[0025] A fourth object of the present invention is to provide a lithium-based liquid battery with high rate performance and long cycle stability, wherein the lithium-based liquid battery uses the above-mentioned vacancy composite diaphragm.

[0026] The fifth object of the present invention is to provide a solid-state battery with high rate performance and long cycle stability, wherein the solid electrolyte used in the solid-state battery is prepared by mixing the colloidal dispersion obtained in step 2 of the above preparation method with a lithium salt and then coating the mixture.

[0027] It is further defined that the mass ratio of the Te vacancy-rich particles, the separator base polymer powder and the lithium salt in the colloidal dispersion is (5-50):100:(50-100).

[0028] Compared with the prior art, the present invention has the following significant effects:

[0029] The present invention provides a preparation method and application of a vacancy composite diaphragm for a lithium-based battery, as well as a lithium-based battery with excellent high-rate performance and long-cycle stability based on the vacancy composite diaphragm. The Te vacancies rich in the diaphragm can effectively capture anions in the electrolyte, promote the rapid migration of lithium ions, and at the same time, can also homogenize lithium ion deposition, effectively inhibit the growth of lithium dendrites, and improve the high-rate performance and long-cycle stability of lithium-ion batteries. In addition, the Te vacancy-rich granular material also has an excellent ability to capture anions when added to a solid electrolyte, and a solid-state battery with excellent rate performance and long-cycle stability can be obtained, which can meet the application requirements of the diaphragm in the field of lithium-ion batteries. The specific advantages are as follows:

[0030] (1) The present invention provides a vacancy composite diaphragm for a lithium-based battery. The introduction of Te-rich vacancy granular material effectively improves the wettability of the diaphragm to the electrolyte and improves the storage capacity of the diaphragm to the electrolyte.

[0031] (2) The invention proposes a vacancy composite separator for lithium-based batteries. The introduction of Te-rich vacancy particle materials effectively limits the migration of anions in the electrolyte, greatly improves the migration ability of lithium ions, and effectively enhances the high-rate performance of lithium-ion batteries.

[0032] (3) The vacancy composite separator for lithium-based batteries proposed in the present invention introduces Te-rich vacancy granular materials, which effectively increases the number of lithium ion migration and uniformizes the deposition of lithium ions, effectively inhibits the growth of lithium dendrites, and improves the long-cycle stability of lithium-ion batteries.

[0033] (4) The present invention adds lithium salt to the colloidal dispersion formed by mixing the diaphragm base polymer powder, Te vacancy-rich particles and organic solvent, and uses it as a composite solid electrolyte in a solid-state battery. It also has the ability to effectively inhibit anion migration, so that the solid-state battery has excellent high-rate performance and long-cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the electron paramagnetic resonance spectrum (EPR) of the Te vacancy-rich particle-bismuth telluride used in Example 1;

[0035] Figure 2 It is a comparison chart of the rate performance of Example 1, Comparative Example 1 and Comparative Example 2;

[0036] Figure 3 The long cycle stability diagram of Example 1, Comparative Example 1 and Comparative Example 2 at 2C current density;

[0037] Figure 4 This is a comparison chart of the rate performance of Example 4 and Comparative Example 3 in a solid-state battery;

[0038] Figure 5 It is a long cycle stability diagram of Example 4 and Comparative Example 3 at 1C current density of solid-state battery. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0040] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0041] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0042] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.

[0043] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0044] Example 1: A vacancy composite diaphragm of this example is prepared by scraping a colloidal diaphragm dispersion prepared from polyvinylidene fluoride-hexafluoropropylene powder, Te-rich vacancy particles-bismuth telluride, acetone and deionized water, wherein the mass ratio of the Te-rich vacancy particles-bismuth telluride to the polyvinylidene fluoride-hexafluoropropylene powder is 5:100, the particle size of the Te-rich vacancy particles-bismuth telluride is 800nm, and the molecular weight of the polyvinylidene fluoride-hexafluoropropylene powder is 600,000.

[0045] The method for preparing the vacancy composite diaphragm of Example 1 is carried out according to the following steps:

[0046] Step 1: Disperse 0.035 g of Te vacancy-rich particle-bismuth telluride in 5.53 g of acetone, and perform ultrasonic treatment at room temperature for 1 h to obtain a Te vacancy-rich particle-bismuth telluride dispersion;

[0047] Step 2: adding 0.7 g of polyvinylidene fluoride-hexafluoropropylene powder to the bismuth telluride dispersion obtained in step 1, and magnetically stirring at 55° C. and 800 r / min for 0.5 h to obtain a colloidal dispersion;

[0048] Step 3: 0.166 g of deionized water was added dropwise to the colloidal dispersion obtained in step 2, and magnetic stirring was performed at 55° C. and 800 r / min for 0.5 h, and the mixture was cooled to room temperature to obtain a colloidal diaphragm dispersion;

[0049] Step 4: Scrape the colloidal diaphragm dispersion obtained in step 3 onto a glass substrate and dry it at room temperature to obtain a vacancy composite diaphragm with a thickness of 15 μm.

[0050] The Te vacancy-rich particle-bismuth telluride used in Example 1 was subjected to an electron paramagnetic resonance (EPR) spectrum test. The test results are as follows: Figure 1 As shown, it can be seen that the material has an obvious strong signal peak at g = 2, which confirms the existence of Te vacancies. Te vacancies have an obvious "trap" effect on anions in the electrolyte, so they can promote the migration of lithium ions, increase the number of lithium ion migration of the composite separator, and improve the rate performance of lithium-ion batteries. At the same time, they can also inhibit the formation of lithium dendrites and improve the long-term cycle stability of lithium-ion batteries.

[0051] Embodiment 2: This embodiment differs from Embodiment 1 in that:

[0052] The mass ratio of the Te-rich vacancy particles-bismuth telluride to the polyvinylidene fluoride-hexafluoropropylene powder is 10:100;

[0053] The specific preparation method is carried out according to the following steps:

[0054] Step 1: Disperse 0.07 g of Te-rich vacancy particle-bismuth telluride in 5.53 g of acetone, and perform ultrasonic treatment at room temperature for 1 h to obtain a Te-rich vacancy particle-bismuth telluride dispersion;

[0055] Step 2: adding 0.7 g of polyvinylidene fluoride-hexafluoropropylene powder to the bismuth telluride dispersion obtained in step 1, and magnetically stirring at 55° C. and 800 r / min for 0.5 h to obtain a colloidal dispersion;

[0056] Step 3: 0.166 g of deionized water was added dropwise to the colloidal dispersion obtained in step 2, and magnetic stirring was performed at 55° C. and 800 r / min for 0.5 h, and the mixture was cooled to room temperature to obtain a colloidal diaphragm dispersion;

[0057] Step 4: Scrape the colloidal diaphragm dispersion obtained in step 3 onto a glass substrate and dry it at room temperature to obtain a vacancy composite diaphragm with a thickness of 15 μm.

[0058] Embodiment 3: This embodiment is different from Embodiment 1 in that:

[0059] The mass ratio of the Te-rich vacancy particles-bismuth telluride to the polyvinylidene fluoride-hexafluoropropylene powder is 18:100;

[0060] The specific preparation method is carried out according to the following steps:

[0061] Step 1: Disperse 0.126 g of Te vacancy-rich particle-bismuth telluride in 5.53 g of acetone, and perform ultrasonic treatment at room temperature for 1 h to obtain a Te vacancy-rich particle-bismuth telluride dispersion;

[0062] Step 2: adding 0.7 g of polyvinylidene fluoride-hexafluoropropylene powder to the bismuth telluride dispersion obtained in step 1, and magnetically stirring at 55° C. and 800 r / min for 0.5 h to obtain a colloidal dispersion;

[0063] Step 3: 0.166 g of deionized water was added dropwise to the colloidal dispersion obtained in step 2, and magnetic stirring was performed at 55° C. and 800 r / min for 0.5 h, and the mixture was cooled to room temperature to obtain a colloidal diaphragm dispersion;

[0064] Step 4: Scrape the colloidal diaphragm dispersion obtained in step 3 onto a glass substrate and dry it at room temperature to obtain a vacancy composite diaphragm with a thickness of 15 μm.

[0065] Comparative Example 1: This embodiment provides a polyvinylidene fluoride-hexafluoropropylene diaphragm, and the preparation method thereof is as follows:

[0066] Step 1, dissolving 0.7 g of polyvinylidene fluoride-hexafluoropropylene in 5.53 g of acetone, stirring magnetically at 55° C. and 800 r / min for 30 min to obtain a transparent colloidal solution;

[0067] Step 2: 0.166 g of deionized water was added dropwise to the transparent colloidal solution obtained in step 1, and magnetic stirring was performed at 55° C. and 1000 r / min for 0.5 h, and the solution was cooled to room temperature to obtain a colloidal diaphragm dispersion;

[0068] Step 3: Scrape the colloidal membrane dispersion obtained in step 2 onto a glass substrate and dry it at room temperature to obtain a pure polyvinylidene fluoride-hexafluoropropylene membrane with a thickness of 15 μm.

[0069] Comparative Example 2: Commercial polypropylene diaphragm Celgard 2500.

[0070] Application Example 1: The diaphragms of Example 1 and Comparative Examples 1-2 are assembled in a lithium-ion battery, wherein the positive electrode is lithium iron phosphate, the negative electrode is lithium foil, and the electrolyte is a mixed solution containing 1 mol / L LiPF6, wherein the solvent is a mixture of ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1.

[0071] Testing: The electrochemical performance of the battery is tested at room temperature.

[0072] Experiment 1: The lithium ion migration number of the lithium battery in Example 1 was characterized. The results are shown in Table 1. It can be seen that the addition of Te vacancy-rich particles-bismuth telluride increased the lithium ion migration number.

[0073] Experiment 2: Test of membrane liquid absorption rate: Weigh the mass of the membrane, then soak the membrane in the electrolyte for 40 minutes, weigh the mass of the membrane before and after soaking in the electrolyte, and the liquid absorption rate is obtained by (mass after soaking - initial mass) / initial mass. The results are shown in Table 1. It can be seen that the addition of Te vacancy-rich particles-bismuth telluride increases the membrane liquid absorption rate.

[0074] Experiment 3: Contact angle tests were performed on the diaphragms in Examples 1-3 and Comparative Examples 1-2. The results are shown in Table 1. It can be seen that the addition of Te-rich vacancy particles-bismuth telluride reduced the contact angle, indicating that the addition of Te-rich vacancy particles-bismuth telluride significantly improved the wettability of the diaphragm to the electrolyte, which is also consistent with the electrolyte absorption rate test results of these diaphragms.

[0075] Test 4: Rate performance and 2C (1C = 170mAg at room temperature (25°C) -1 ) were tested for cycle performance, and the results are shown in Figure 2-3 From Table 1, it can be seen that the rate performance and long-term cycle stability of the vacancy composite separator using Example 1 of the present invention are more excellent.

[0076] Table 1 Diaphragm and battery performance test data

[0077] Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Lithium ion migration number 0.36 0.34 0.62 0.61 0.59 Contact angle (°) 24 60 19 19 20 Diaphragm liquid absorption rate (%) 210 122 217 210 208 Battery capacity retention rate after 500 cycles at 25℃ / 2C (%) 0 59.4 82.7 79.1 70.8 <![CDATA[Battery specific capacity (mAh g -1 ) at 25℃ / 15C 4 28 69 61 53

[0078] Example 4: A method for preparing a composite solid electrolyte of this example is as follows:

[0079] Step 1: Disperse 0.05 g of Te-rich vacancy particle-bismuth telluride in 15.42 g of nitrogen-methylpyrrolidone, and perform ultrasonic treatment at room temperature for 1 h to obtain a Te-rich vacancy particle-bismuth telluride dispersion;

[0080] Step 2: Add 1 g of polyvinylidene fluoride-hexafluoropropylene powder to the Te vacancy-rich particle-bismuth telluride dispersion obtained in step 1, and stir magnetically at room temperature and 800 r / min for 12 h to obtain a colloidal dispersion;

[0081] Step 3: Under the protection of a dry argon atmosphere, 0.8 g of lithium bis(trifluoromethylsulfonyl)imide was added to the slurry of step 2, and the mixture was stirred in a closed manner throughout the process to avoid prolonged contact with air and moisture;

[0082] Step 4: Scrape the colloidal dispersion obtained in step 3 onto a glass substrate, and vacuum dry at 60 degrees for 48 hours to obtain a composite solid electrolyte with a thickness of 60 μm.

[0083] Comparative Example 3: This comparative example provides a pure polyvinylidene fluoride-hexafluoropropylene solid electrolyte. The difference between this comparative example and Example 4 is that Te vacancy-rich particles-bismuth telluride are not added to the solid electrolyte. Other steps and parameters are the same as those in Example 4.

[0084] Application Example 2: The solid electrolytes of Example 4 and Comparative Example 3 are assembled in a lithium-ion battery, wherein the positive electrode is lithium iron phosphate, the negative electrode is lithium foil, and the solid electrolytes between the positive and negative electrodes are Example 4 and Comparative Example 3, respectively.

[0085] Testing: The electrochemical performance of the battery is tested at room temperature.

[0086] Test 5: Rate performance and 1C (1C = 170mAg at room temperature (25°C) -1 ) was used to test the long cycle performance under the condition of Figure 4-5 It can be seen that the solid-state battery rate performance and long-cycle cycle stability using the composite solid electrolyte of Example 4 of the present invention are more excellent.

Claims

1. A vacancy composite diaphragm, characterized in that: The invention is prepared by coating a colloidal diaphragm dispersion prepared from diaphragm base polymer powder, Te-rich vacancy particles, an organic solvent and deionized water. The Te-rich vacancy particles are one or a mixture of several of bismuth telluride, N-type bismuth telluride and P-type bismuth telluride. The mass ratio of the Te-rich vacancy particles to the diaphragm base polymer powder is (5-50):

100.

2. The vacancy composite diaphragm according to claim 1, characterized in that: The membrane substrate polymer powder is one or a mixture of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-chlorotrifluoroethylene, polyacrylic acid and polyacrylonitrile.

3. The method for preparing the vacancy composite diaphragm according to claim 1 or 2, characterized in that: The method proceeds as follows: Step 1: Disperse the Te vacancy-rich particles in an organic solvent and perform ultrasonic treatment at room temperature for 1 h to 3 h to obtain a Te vacancy-rich particle dispersion; Step 2: adding the membrane base polymer powder to the Te vacancy-rich particle dispersion of step 1, and magnetically stirring at 50-70° C. for 0.5 h-1 h to obtain a colloidal dispersion; Step 3: Add deionized water dropwise to the colloidal dispersion of step 2, stir magnetically at 50-70° C. for 0.5 h-1 h, and cool to room temperature to obtain a colloidal diaphragm dispersion; Step 4: Scrape the colloidal diaphragm dispersion of step 3 onto the substrate and dry it at room temperature to obtain a vacancy composite diaphragm.

4. The method according to claim 3, characterized in that: The organic solvent in step 1 is one or a mixture of acetone, N-methylpyrrolidone, NN dimethylformamide, NN dimethylacetamide, the mass ratio of the diaphragm base polymer powder to the organic solvent in step 1 in step 2 is 1: (6-10), and the mass ratio of deionized water to the organic solvent in step 1 in step 3 is (3-5):

100.

5. The method according to claim 3, characterized in that: In step 4, the thickness of the vacant composite diaphragm is 8 to 50 μm.

6. Use of the vacancy composite diaphragm according to claim 1 or 2 in a lithium-based liquid battery.

7. The use according to claim 6, characterized in that: Lithium-based liquid batteries include lithium metal batteries, lithium-ion batteries, lithium-sulfur batteries, lithium-based dual-ion batteries and lithium-CO2 batteries.

8. A lithium-based liquid battery with excellent high rate performance and long cycle stability, characterized in that: It uses the vacancy composite diaphragm described in claim 1 or 2.

9. A solid-state battery with excellent high rate performance and long cycle stability, characterized in that: The solid electrolyte used is prepared by mixing the colloidal dispersion obtained in step 2 of the method described in any one of claims 3 to 5 with a lithium salt and then coating the mixture.

10. The solid-state battery according to claim 9, characterized in that: The mass ratio of Te vacancy-rich particles, separator substrate polymer powder and lithium salt in the colloidal dispersion is (5-50):100:(50-100).

Citation Information

Patent Citations

  • Intercalation material for lithium-sulfur battery

    CN109920957A

  • Piezoelectric composite diaphragm for lithium metal battery as well as preparation method and application of piezoelectric composite diaphragm

    CN114520396A